EFFICACY OF GASTRIC ASPIRATION IN REDUCING POST-TONSILLECTOMY VOMITING IN CHILDREN - Muhammad, Raza; Wadood, Fazal; Haroon, Tahir; Khan, Zakir; Shah, Imran (Journal of Ayub Medical College Abbottabad, 2012)
Background: Nausea and vomiting are two of the most frequently experienced postoperative side effects complicating one third of the cases. The objective of this study was to determine the effectiveness of gastric decompression in reducing the incidence and complications associated with post-tonsillectomy vomiting in children. Methods: This was a randomised control study conducted at the ENT Department, Ayub Teaching Hospital Abbottabad from January to June 2012. Patients included in this study were divided into two groups, group A undergoing gastric aspiration and group B not undergoing gastric aspiration. Gastric aspiration was done with an oro-gastric tube placed under direct visualisation while the patient was still under general anaesthesia. The incidence of vomiting, episodes of vomiting and the need for rescue anti-emetic prophylaxis were noted. Results: A total of 54 patients were included in the study. Their ages ranged from 5 to12 years with mean age 7.85±2.18 years. No statistically significant difference (p>0.05) was noted between the two groups for the patients experiencing vomiting (33% vs 41%, p=0.389), the mean number of episodes of vomiting (0.71 vs 0.88, p=0.555), and patients requiring rescue anti-emetics (11% vs 15%, p=0.500). Conclusion: Gastric aspiration during tonsillectomy is not useful in reducing post-tonsillectomy vomiting. Keywords: Gastric aspiration, Tonsillectomy, Vomiting, Postoperative